Examining Power Quality Challenges in Photovoltaic-Grid Integration: A Critical Review - Sandi, Zakariya (Journal of Power, Energy, and Control, 2024)
With the massive growth of photovoltaic (PV) installations worldwide, the impact of integration between PV and the grid is becoming a serious issue and requires immediate attention. This is due to the intermittent power that the PV itself generates. The quality of the power can affect the stability of the system, the protection equipment, and the energy efficiency, which imposes a financial issue. This literature review will present the most frequently encountered problems when PV integrates with the grid, namely power quality issues, particularly on the distribution network. Problem-solving will also be presented as a reference for future PV development. It discusses several ways to handle power quality problems, depending on the factors influencing power quality. One of the proven ways is to use a modern inverter equipped with features that suit the system's needs. However, the discussion in this paper is limited to the issues of power quality and voltage generated by PV integrated into the grid. Future studies can discuss other technical issues, such as protection, feeder losses, and other problems that may arise in the future.